Case Study of Corporate Team Dynamics: Taking Nongfu Spring as An Example - Ge, Xuanyi (International Journal of Global Economics and Management, 2024)
This paper takes Nongfu Spring Company as an example and analyses its strategic management and team dynamics in depth. At the strategic management level, Nongfu Spring has built a solid and sustainable competitive advantage by virtue of its keen market insight and flexible strategic layout. The company adopts a strategy that combines growth and differentiation with precise market positioning to provide strong support for long-term development. In terms of team dynamics, this paper explores the formation process, development trajectory and decision-making mechanism of the Nongfu Spring team. The study shows that the Nongfu Spring team demonstrates excellent collaborative ability and efficient decision-making efficiency, and this efficient teamwork not only stimulates the team’s innovation ability, but also significantly improves its flexibility and adaptability in response to market changes, which enables Nongfu Spring to consistently occupy an advantageous position in the fierce market competition.